Penerapan Lima Model Kesetimbangan Adsorpsi Isoterm pada Adsorpsi Ion Logam Chrom VI oleh Zeolit - Syarifah Aini; Supratikno Supratikno (Eksergi, 2018)
Chrom VI metal ion include heavy metal waste which needs further processing using adsorbent. Zeolite is a suitable adsorbent for absorbing strong affinity chrom VI metal ions because zeolite is a natural mineral that has an active surface area per unit of mass and power. The purpose of this study was to determine a suitable model for the equilibrium adsorption of chrom VI metal ion by zeolite along with their parameter values, and to determine the optimal zeolite absorption against chrom VI metal ion. This study uses the method of applying the isotherm adsorption equilibrium model which includes 5 equations namely Linear Adsorption (Henry's Law), Freundlich Isotherm Adsorption, Langmuir Isoterm Adsorption, Brunauer-Emmett-Teller Isotherm (BET), Sigmoidal Chapman Equation. From these five models, data fitting is done to find models that are closer to the data. Data matching is done by minimizing the Matlab program. The results showed that the suitable model is the BET Isotherm Adsorption model with parameter values, namely the BET isotherm adsorption constant value (CBET) of 0.5183 l/mg, the maximum capacity of the adsorbent at equilibrium theoretical (qs) is 149.9977 mg/g and the saturated adsorbate concentration in the monolayer (Cs) is 184.1691 mg l.